The Role of Pokdarwis in Product Development of Lusi Island Tourism Objects - Novitasari, Yurike; Rodiyah, Isnaini (Indonesian Journal of Public Policy Review, 2022)
This study aims to analyze and describe the role of Pokdarwis in the development of Lusi Island tourism objects and to analyze and describe the constraints on the role of Pokdarwis in developing Lusi Island tourism objects in Kedungpandan, Jabon District, Sidoarjo Regency. This study uses the theory of the role of Pokdarwis according to Rahim. The research method uses a qualitative descriptive approach using data collection techniques in the form of observation, interviews, and documentation. Data analysis techniques from Miles & Huberman in Sugiyono (2015:246-253). Which consist of data collection, data presentation, data reduction, and drawing conclusions. The results of this study indicate that the role of Pokdarwis in the development of Lusi Island tourism is seen from the theory of the role of Pokdarwis, namely product development, Pokdarwis only maintains existing facilities because of the limited authority in procuring facilities at the Ministry of Maritime Affairs and Fisheries. Lusi Island tourism promotion is carried out through social media and in collaboration with travel agents, the Association of Sidoarjo Travel Companies, and related agencies. Limited funds and lack of coordination made Pokdarwis unable to maximize the development of Lusi Island Tourism.